Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2022)
A dataset containing 48683 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Acorus calamus L." ] } The dataset includes 48683 records from 504 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0196951-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences